C.E. Credit. Why Integrate Dentistry and Behavioral Health: What Every Oral Health Provider Should Know About Mental Health and Substance Use - Rachael Matulis; Adrienne Lapidos; Sarah Neil Mockridge; Danielle Rulli (Taylor & Francis Group, 2024)
Background Mental health and substance use challenges have reached crisis levels in the U.S. Nearly one in three American adults had either a substance use disorder or any mental illness in 2022, and nearly one in four adolescents aged 12 to 17 had a substance use disorder or major depressive episode in the same year. The behavioral health workforce is not able to keep up with this demand, leading to a scarcity of resources and services for individuals with mental health and substance use needs. This need increasingly impacts all health care settings, including dental settings, where providers often have limited resources and supports for addressing the mental health and substance use needs of patients - here referred to with the umbrella term of "behavioral health."Discussion Because of the bi-directional relationship between oral health and behavioral health, providing high-quality dental care often involves considering many aspects of a person's health, particularly the behavioral health factors that influence oral health. Mental health challenges such as depression, anxiety, or a substance use disorder can negatively impact oral health, and the reverse is also true; poor oral health can create or worsen challenges with behavioral health. This paper provides an overview of the bidirectional connections between oral health and behavioral health, and reviews disparities facing marginalized communities who lack access to care. It also offers promising practices and key resources for dental providers interested in better integrating oral health and behavioral health services.Continuing Education Credit Available The practice worksheet is available online in the supplemental material tab for this article. A CDA Continuing Education quiz is online for this article:https://www.cdapresents360.com/learn/catalog/view/20